Paeoniflorin Resists H2O2-Induced Oxidative Stress in Melanocytes by JNK/Nrf2/HO-1 Pathway - Yuan, Jinping; Lu, Yansong; Wang, Hexiao; Feng, Yuxin; Jiang, Shibin; Gao, Xing-Hua; Qi, RuiQun; Wu, Yan; Chen, Hong-Duo (Frontiers in Pharmacology, 2020)
Paeoniflorin (PF) possesses multiple biological functions including anti-oxidization. PF is the major bioactive ingredient of total glycosides of paeony (TGP), which could promote re-pigmentation of vitiligo. The study was sought to investigate the effects and potential signaling pathways of PF on hydrogen peroxide (H2O2)-induced oxidative stress in melanocytes. The results showed that pretreatment with 50 µM PF significantly inhibited cell apoptosis, enhanced cell viability, and suppressed reactive oxygen species (ROS) accumulation by enhancing the productions of superoxide dismutase (SOD) and antioxidant enzymes catalase (CAT). Furthermore, PF activated c-Jun amino terminal kinase (JNK) and the nuclear factorE2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) pathway to counteract H2O2-induced oxidative damage in PIG1 and PIG3V. Taken together, our study firstly demonstrates that PF resists H2O2-induced oxidative stress in melanocytes probably by activating JNK/Nrf2/HO-1 signaling, suggesting a potential therapeutic application of PF on vitiligo.